Carbon scaffold with controllable small pore structure based on mask projection stereolithography. (September 2021) - Wang, Yaning; Chen, Ruomeng; Chen, Xu; Hu, Huiwu; Li, Tengfei; Liu, Yaxiong; Duan, Yugang
Abstract: Mask Projection Stereolithography (MPSL), due to its high printing resolution, is suitable for fabricating porous polymer architectures that are used as carbon scaffold precursors. In the present work, a carbon scaffold with a controllable small porous structure was fabricated by MPSL. A polymer lattice structure used as the carbon scaffold precursor was first fabricated by MPSL. Sodium chloride was selected as the granular support, and nano-silica particles were introduced into the granular support so that sodium chloride could easily fill the lattice structure. A carbon scaffold with controllable low shrinkage (41.3%) and a small porous structure (skeleton thickness = 40 µ m and pore size = 300 µ m ) was obtained by pyrolyzing the polymer lattice structure in the granular support, and subsequently, it was processed by hydrofluoric acid (HF). The unprocessed and HF-processed scaffolds were both composed of simple substance carbon, and silicon oxide particles embedded on the unprocessed scaffold were cleaned by HF. Finally, the compressive properties of the scaffold were examined. The fracture appearances of the scaffold under the application of compressive forces parallelly and vertically to the stacking direction were different, and compressive properties in vertical to the stacking direction were superior to those in parallel to the stacking direction. Therefore, it can be inferred that the proposed method is effective in fabricating multi-scale carbon scaffolds with small controllable porous structures based on stress analysis to obtain optimum mechanical properties, which makes it a promising material for many applications. Graphical Abstract: ga1 Highlights: ● A method is proposed to develop carbon scaffold with controllable small pore structure. ● The volume shrinkage, skeleton thickness and pore size of the scaffold were 41.3%, 40 μ m and 300 μ m, respectively. ● The compressive property of the scaffold shows anisotropy. ● This method has potential to fabricate multi-scale porous carbon scaffold with optimum mechanical properties.